Effects of electropulsing treatment on material properties and ultra-precision machining of titanium alloy. Issue 9 (February 2016) - Wu, Hong; To, Sandy
Abstract Titanium alloy is well known with difficult machinability, which limits its application unavoidably. In this study, electric pulse treatment (EPT) is firstly employed to change the material properties and improve the machinability of titanium alloy Ti6Al4V in ultra-precision machining. A series of tests of EPT and ultra-precision cutting have been carried out. Effects of EPT parameters on microstructure and mechanical properties of Ti6Al4V have been investigated. The chip morphology, cutting force, and surface roughness of titanium alloys after EPT and without EPT in ultra-precision machining have been analyzed, too. It was found that EPT technology can improve the machinability of titanium alloy in ultra-precision machining and the machinability of titanium alloy becomes better with the increasing of current density and frequency of EPT.